Conductive paste and cured product
By using epoxy resin, latent curing agent and plate-like crystalline metal powder with specific particle size in the conductive paste, the problem of taking into account both conductivity and adhesion is solved, and the high conductivity of the conductive paste is achieved. Commodity and strong adhesive force, suitable for fixing and grounding of electronic components.
Patent Information
- Application Number
- CN202380032799.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-15
- Filing Date
- 2023-04-11
- Publication Date
- 2024-12-17
AI Technical Summary
In the process of reducing the connection resistance value of the existing conductive paste, the proportion of resin components is reduced, resulting in a decrease in adhesive force, making it difficult to take into account both conductivity and adhesive force.
The conductive paste containing epoxy resin, a latent curing agent and a plate-like crystalline metal powder with an average particle size of 0.6 to 1.4 μm is used to improve the conductivity and adhesion of the cured substance by adjusting the component ratio and particle size. .
It achieves excellent balance between conductivity and adhesive force, ensures high conductivity and strong adhesive force of the conductive paste, and is suitable for fixing and grounding of electronic components.
Smart Images

Figure BDA0005072784030000301
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive paste and a cured product thereof in which both conductivity and adhesive strength of the resulting cured product are achieved. Background Art
[0002] In the past, conductive pastes were used for fixing and grounding (earthing; grounding) of electrical / electronic components such as smart phones and electronic mobile devices. In recent years, for the grounding of electronic components, a low-resistance conductive paste is desired to facilitate conduction, and the following technology is particularly desired: as conductivity, not only the resistance value (volume resistivity) of the resin (conductive paste) itself is low, but also the resistance (connection resistance value) generated between the adherend and the conductive paste can be reduced. In response to such requirements, it is known that the resistance value of the conductive paste can be reduced by using single-crystal conductive particles (for example, Japanese Patent Publication No. 2016-160415, Japanese Patent Publication No. 2016-065146). Summary of the invention
[0003] However, since the conductive paste contains a large amount of conductive particles as a solid substance in order to reduce the connection resistance value, there is a problem that the ratio of the resin component contained therewith decreases, and the adhesive force decreases.
[0004] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a conductive paste having an excellent balance between conductivity and adhesive strength of the resulting cured product. Another object of the present invention is to provide a cured product using the conductive paste.
[0005] The present inventors have conducted intensive studies to achieve the above-mentioned object and, as a result, have found a method for obtaining a conductive paste capable of achieving both conductivity and adhesive strength of the resulting cured product, thereby completing the present invention.
[0006] Hereinafter, the gist of the present invention will be described. One embodiment of the present invention for solving the above-mentioned problems relates to the following conductive paste.
[0007] [1] A conductive paste comprising the following components (A) to (C),
[0008] (A) ingredient: epoxy resin;
[0009] (B) component: latent curing agent;
[0010] (C) Component: plate-like crystalline metal powder having an average particle size of 0.6 to 1.4 μm.
[0011] [2] The conductive paste according to [1], comprising 20 to 150 parts by mass of the component (C) based on 100 parts by mass of the component (A).
[0012] [3] The conductive paste according to [1] or [2], wherein the specific surface area of the component (C) is 0.1 to 1.8 m 2 / g.
[0013] [4] The conductive paste according to any one of [1] to [3], further comprising a metal powder other than the component (C) as the component (D).
[0014] [5] The conductive paste according to [4], comprising 50 to 500 parts by mass of the component (D) based on 100 parts by mass of the component (A).
[0015] [6] The conductive paste according to any one of [1] to [5], wherein the component (A) contains a monofunctional epoxy resin.
[0016] [7] The conductive paste according to any one of [1] to [6] above, further comprising rubber particles.
[0017] [8] The conductive paste according to [4] or [5] above, which is essentially composed of the above-mentioned (A) to (D) components and at least one selected from the group consisting of a filler (preferably rubber particles), a storage stabilizer, a metal complex and a resin.
[0018] [9] The conductive paste according to [4] or [5] above, which is essentially composed of the above-mentioned components (A) to (D) and at least one selected from the group consisting of a filler (preferably rubber particles), a storage stabilizer and a resin.
[0019]
[10] The conductive paste according to [4] or [5] above, which is essentially composed of the above-mentioned components (A) to (D), a filler (preferably rubber particles), a storage stabilizer and a resin.
[0020]
[11] The conductive paste according to [4] or [5] above, which is essentially composed of the above-mentioned components (A) to (D), a filler (preferably rubber particles) and a storage stabilizer.
[0021]
[12] A cured product obtained by curing the conductive paste according to any one of [1] to
[11] above.
[0022] Moreover, another aspect of the present invention for solving the above-mentioned problems relates to the following conductive paste.
[0023] [1'] A conductive paste comprising the following components (A) to (C),
[0024] (A) ingredient: epoxy resin;
[0025] (B) component: latent curing agent;
[0026] (C) Component: crystalline metal powder having an average particle size of 0.6 to 1.4 μm.
[0027] In the conductive paste described in [1'] above, preferred embodiments include the embodiments [2] to
[12] . Furthermore, in the conductive paste described in [1'] above, the following description of each component is used for the description other than the description on the shape of the component (C). DETAILED DESCRIPTION
[0028] Next, the details of the present invention will be described. It should be noted that the present invention is not limited to the following embodiments, but can be variously modified within the scope of the technical solution. In addition, the embodiments described in this specification can be combined arbitrarily to form other embodiments.
[0029] Throughout this specification, as far as the expression in singular form is concerned, unless otherwise specified, it should be understood that the singular form also includes the concept of its plural form. Therefore, unless otherwise specified, it should be understood that the article in the singular form (for example, "a", "an", "the", etc. in English) also includes the concept of its plural form. In addition, for the terms used in this specification, unless otherwise specified, it should be understood that they are used with the meaning commonly used in the field. Therefore, unless otherwise defined, all professional terms and scientific and technological terms used in this specification have the same meaning as those commonly understood by those skilled in the art in the field to which the invention belongs. In the event of a conflict, this specification (including definitions) takes precedence.
[0030] In this specification, "X to Y" is used to mean including the numerical values (X and Y) recorded before and after as the lower limit and upper limit, respectively, and means "above X and below Y". In addition, in this specification, the term "(meth)acrylic" refers to both acrylic and methacrylic. In addition, unless otherwise specified, the concentration and % represent the mass concentration and mass %, respectively, and the ratio is set as the mass ratio unless otherwise specified. In addition, unless otherwise specified, the operation and measurement of physical properties are carried out under the conditions of room temperature (20°C to 25°C) / relative humidity 40%RH to 55%RH. In addition, "A and / or B" means including A, B individually and their combinations.
[0031] [Conductive paste]
[0032] The conductive paste according to one embodiment of the present invention (hereinafter, also simply referred to as "the conductive paste according to the present invention" or "the conductive paste") contains the following components (A) to (C),
[0033] (A) ingredient: epoxy resin;
[0034] (B) Component: Latent curing agent
[0035] (C) Component: plate-like crystalline metal powder having an average particle size of 0.6 to 1.4 μm.
[0036] That is, the conductive paste of the present invention contains the above-mentioned (A) to (C) components. By having such a composition, the conductive paste of the present invention has excellent conductivity and adhesion. The details of the mechanism are not yet clear, but it is considered that by making the average particle size of the crystalline metal powder contained as the (C) component of the present invention 0.6 to 1.4 μm, the conductivity and adhesion of the cured product can be improved in a balanced manner. When the average particle size of the crystalline metal powder corresponding to the (C) component is less than 0.6 μm, the conductivity decreases (Comparative Example 2 described later). On the other hand, when the average particle size exceeds 1.4 μm, there is a tendency that not only the conductivity of the cured product decreases, but also the adhesion decreases (Comparative Examples 3 and 4 described later). Furthermore, the inventors of the present invention have also found that when the conductive paste contains fine metal powder, although the adhesion is generally reduced, the conductive paste of the present invention containing fine metal powder such as the (C) component still has excellent adhesion. Although the details of the mechanism of such improvement in adhesive force are not clear, it is considered that the above-mentioned effect of improving adhesive force can be obtained by using crystalline metal powder as the (C) component.
[0037] It should be noted that the above mechanism is based on speculation, and the correctness of the mechanism does not affect the technical scope of the present invention.
[0038] Hereinafter, each component contained in the conductive paste will be described.
[0039] <(A)Component>
[0040] The component (A) contained in the conductive paste of the present invention is an epoxy resin. As the component (A), there is no particular limitation as long as it is a compound having one or more epoxy groups in one molecule. It should be noted that, as described in the (silane coupling agent) item described later, the component (A) does not contain a compound containing silicon atoms in addition to one or more epoxy groups. From the perspective of excellent curing properties, the component (A) preferably contains a compound having two or more epoxy groups in one molecule (multifunctional epoxy resin). That is, the component (A) preferably contains a multifunctional epoxy resin having two or more epoxy groups in one molecule. For such a compound (multifunctional epoxy resin), the upper limit of the number of epoxy groups contained in one molecule is not particularly limited, and is preferably 6 or less. As an example, the number of epoxy groups contained in the compound as the component (A) is preferably 2 to 6 (2 to 6 functional epoxy resins), more preferably 2 to 3 (2 to 3 functional epoxy resins), and particularly preferably 2 (2 functional epoxy resins). In addition, the epoxy group may be contained in the compound (epoxy resin) in the form of a glycidyl group.
[0041] In addition, the compound used as component (A) may be solid or liquid, and is preferably liquid from the viewpoint of excellent operability. It should be noted that in this specification, "liquid" refers to a state (liquid) having fluidity at 25°C. Specifically, "liquid at 25°C" refers to the viscosity of the liquid at 25°C using a cone-plate rotational viscometer at a shear rate of 10s -1 The viscosity measured is 1000 Pa·s or less. It should be noted that in this specification, the viscosity of the components is measured using a cone-plate type rotational viscometer at a shear rate of 10 s -1 As an example, the viscosity of the multifunctional epoxy resin used as the component (A) at 25°C is preferably 0.01 Pa·s or more and less than 1000 Pa·s, more preferably 0.1 to 500 Pa·s, further preferably 0.3 to 100 Pa·s, particularly preferably 0.5 to 10 Pa·s, and most preferably 0.8 to 5 Pa·s.
[0042] The epoxy equivalent of the multifunctional epoxy resin used as component (A) is not particularly limited. From the viewpoint of further improving the adhesive force, it is preferably 50 g / eq or more and less than 210 g / eq, more preferably 100 g / eq or more and less than 210 g / eq, and particularly preferably 130 g / eq or more and less than 180 g / eq. It should be noted that in this specification, the epoxy equivalent is a value measured in accordance with JIS K-7236:2001. In addition, when the epoxy equivalent cannot be obtained by this method, it can also be calculated in the form of a value obtained by dividing the molecular weight of the target epoxy resin (compound) by the number of epoxy groups contained in one molecule of the epoxy resin (compound).
[0043] Specific examples of the multifunctional epoxy resin used as component (A) include bisphenol epoxy resins; alkylene glycol epoxy resins; novolac epoxy resins such as phenol novolac epoxy resins and cresol novolac epoxy resins; glycidylamine compounds; naphthalene epoxy resins having four glycidyl groups, etc. These may be used alone or in combination of two or more, and component (A) preferably includes a bisphenol epoxy resin from the viewpoint of excellent conductivity.
[0044] As long as the bisphenol epoxy resin is an epoxy resin with a bisphenol skeleton, it is not particularly limited. As the bisphenol epoxy resin, for example, bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol AD epoxy resin, hydrogenated bisphenol A epoxy resin, hydrogenated bisphenol F epoxy resin, urethane modified bisphenol epoxy resin, rubber modified bisphenol epoxy resin, polyoxyalkylene modified bisphenol epoxy resin, etc. can be cited. They can be used alone, or two or more can be used in combination, from the aspect of excellent conductivity and operability, preferably bisphenol A epoxy resin and bisphenol F epoxy resin are used in combination. That is, the bisphenol epoxy resin included as (A) component preferably includes bisphenol A epoxy resin and bisphenol F epoxy resin, more preferably bisphenol A epoxy resin and bisphenol F epoxy resin.
[0045] The compound (multifunctional epoxy resin) as component (A) may be any of synthetic products or commercial products. Commercial products of bisphenol-type epoxy resins are not particularly limited, and examples thereof include jER (registered trademark) 828, 1001, 801, 806, 807, YX8000, YX8034, YX4000 (manufactured by Mitsubishi Chemical Corporation), EPICLON (registered trademark) 830, 850, EXA-830CRP, EXA-830LVP, EXA-850CRP, EXA-835LV (manufactured by DIC Corporation), ADEKA RESIN (registered trademark) EP4100, EP4000, EP4080, EP4085, EP4088, EPU6, EPU7N, EPR4023, EPR1309, EP4920 (manufactured by ADEKA Co., Ltd.), TEPIC (registered trademark) (manufactured by Nissan Chemical Co., Ltd.), KF-101, KF-1001, KF-105, X-22-163B, X-22-9002 (manufactured by Shin-Etsu Chemical Co., Ltd.), DENACOL (registered trademark) EX411, 314, 201, 212, 252 (manufactured by Nagase ChemteX Corporation), DER-331, 332, 334, 431, 542 (manufactured by Dow Chemical Co., Ltd.), YH-434, YH-434L (manufactured by Nippon Steel Sumitomo Chemical Co., Ltd.), etc. These may be used alone or in combination of two or more.
[0046] As component (A), a rubber-dispersed epoxy resin can be used. A rubber-dispersed epoxy resin is an epoxy resin in which rubber particles are dispersed. When such a rubber-dispersed epoxy resin is used, the epoxy resin contained therein is included in component (A). That is, component (A) may include an epoxy resin that is a resin component in the rubber-dispersed epoxy resin, or may be an epoxy resin that is a resin component in the rubber-dispersed epoxy resin.
[0047] When a rubber-dispersed epoxy resin is used as the component (A), the rubber particles contained in the rubber-dispersed epoxy resin can function as a filler described later. Therefore, by mixing such a form of the component (A) with the components (B) to (C) described later, and the component (D) and any other components added as needed, a conductive paste containing a filler can be prepared. The rubber particles may be particles consisting of only one layer showing rubber elasticity, or particles having a multilayer structure having at least one layer showing rubber elasticity (for example, core-shell particles). In addition, the rubber particles may be dispersed in the epoxy resin in advance before use. At this time, specifically, the rubber particles may be dispersed in the epoxy resin using a mixing and stirring device such as a high-power homogenizer, or the rubber particles may be synthesized in the epoxy resin by emulsion polymerization. As the polymer constituting the rubber particles dispersed together with the epoxy resin as the component (A), for example, butadiene rubber, acrylic rubber, silicone rubber, butyl rubber, olefin rubber, styrene rubber, NBR (nitrile rubber), SBR (styrene butadiene rubber), IR (isoprene rubber), EPR (ethylene propylene rubber), etc. can be used. These can be used alone or in combination of two or more.
[0048] Commercially available products of the rubber dispersed epoxy resin include KaneAce (registered trademark) MX-153, MX-136, MX-257, MX-127, MX-451 (manufactured by KANEKA CORPORATION), ACRYSET (registered trademark) BPF-307, BPA-328 (manufactured by Nippon Shokubai Co., Ltd.), etc. These may be used alone or in combination of two or more.
[0049] When the storage stabilizer as an optional component described below is in a form dispersed in the epoxy resin, the epoxy resin contained therein is included in the component (A).
[0050] From the aspect of excellent operability, component (A) preferably contains a monofunctional epoxy resin. That is, in a preferred embodiment, component (A) contains a monofunctional epoxy resin in addition to the above-mentioned compound (multifunctional epoxy resin) having two or more epoxy groups in one molecule. Monofunctional epoxy resin is not particularly limited as long as it is a compound having one epoxy group in one molecule. It should be noted that the epoxy group can be contained in the compound (epoxy resin) in the form of a glycidyl group. By adding a monofunctional epoxy resin, the viscosity of component (A) and the conductive paste can be adjusted, and the conductive paste can be easily prepared. In addition, the operability when using it can be improved.
[0051] The viscosity of the monofunctional epoxy resin used as the component (A) at 25° C. is preferably 1 to 500 mPa·s, more preferably 3 to 100 mPa·s, and particularly preferably 5 to 50 mPa·s, from the viewpoint of adjusting the viscosity of the resulting conductive paste and further improving workability.
[0052] From the same viewpoint as above, the epoxy equivalent of the monofunctional epoxy resin used as the component (A) is preferably 100 to 500 g / eq, more preferably 150 to 350 g / eq, and most preferably 200 to 300 g / eq. By including a monofunctional epoxy resin having such an epoxy equivalent as the component (A), a conductive paste having a low viscosity and excellent workability can be obtained.
[0053] Examples of the monofunctional epoxy resin include methyl glycidyl ether, ethyl glycidyl ether, n-butyl glycidyl ether, isobutyl glycidyl ether, phenyl glycidyl ether, 2-ethylhexyl glycidyl ether, decyl glycidyl ether, stearyl glycidyl ether, allyl glycidyl ether, 2-methyloctyl glycidyl ether, methoxypolyethylene glycol monoglycidyl ether, ethoxypolyethylene glycol monoglycidyl ether, butoxypolyethylene glycol monoglycidyl ether, phenoxypolyethylene glycol monoglycidyl ether, p-tert-butylphenyl glycidyl ether, sec-butylphenyl glycidyl ether, n-butylphenyl glycidyl ether, phenylphenol glycidyl ether, aliphatic / aromatic glycidyl ethers such as water glyceryl ether, cresol glycidyl ether, dibromocresol glycidyl ether, 1,4-butanediol diglycidyl ether, n-butyl glycidyl ether, allyl glycidyl ether, 2-ethylhexyl glycidyl ether, phenyl glycidyl ether, cresol glycidyl ether, p-sec-butylphenyl glycidyl ether, tert-butylphenyl glycidyl ether, diglycidyl ether, (poly)ethylene glycol glycidyl ether, and butanediol glycidyl ether; aliphatic / aromatic glycidyl esters such as neodecanoic acid glycidyl ester and methacrylate glycidyl ester; compounds having a glycidyl group as a functional group such as styrene oxide, etc. Among them, from the viewpoint of storage stability and conductivity, the monofunctional epoxy resin preferably contains at least one selected from aliphatic / aromatic glycidyl ethers and aliphatic / aromatic glycidyl esters, more preferably contains at least one selected from aliphatic / aromatic glycidyl esters, and particularly preferably contains at least one selected from aliphatic glycidyl esters. These may be used alone or in combination of two or more. Among them, glycidyl neodecanoate is preferably contained from the viewpoint of excellent storage stability and conductivity.
[0054] The monofunctional epoxy resin may be a synthetic product or a commercial product. Examples of commercial products of the monofunctional epoxy resin include, but are not limited to, EPIOL (registered trademark) TB manufactured by NOF Corporation and CARDURA (registered trademark) E10P manufactured by MOMENTIVE.
[0055] In one embodiment, the component (A) preferably comprises a bisphenol epoxy resin (preferably a bisphenol A epoxy resin and a bisphenol F epoxy resin), and at least one selected from aliphatic / aromatic glycidyl ethers and aliphatic / aromatic glycidyl esters.
[0056] In one embodiment, the component (A) more preferably contains a bisphenol epoxy resin (preferably a bisphenol A epoxy resin and a bisphenol F epoxy resin) and at least one selected from aliphatic glycidyl esters.
[0057] In one embodiment, the component (A) particularly preferably contains a bisphenol epoxy resin (preferably a bisphenol A epoxy resin and a bisphenol F epoxy resin) and glycidyl neodecanoate.
[0058] When the component (A) contains a monofunctional epoxy resin, the content of the monofunctional epoxy resin is preferably 1% to 50% by mass, more preferably 5% to 40% by mass, and most preferably 10% to 30% by mass relative to the entire component (the total mass of the component (A) being 100% by mass). When the content is 1% by mass or more, the workability and conductivity are further improved, and when the content is 50% by mass or less, a conductive paste having excellent storage stability can be obtained.
[0059] In component (A), the mass ratio of the polyfunctional epoxy resin to the monofunctional epoxy resin (mass of the polyfunctional epoxy resin:mass of the monofunctional epoxy resin) is preferably 95:5 to 50:50, more preferably 90:10 to 60:40, and particularly preferably 85:25 to 70:30.
[0060] It should be noted that, when two or more epoxy resins are used as component (A), the content of component (A) refers to their total amount. In addition, when two or more multifunctional epoxy resins are used, the content of multifunctional epoxy resins refers to their total amount. Furthermore, when two or more monofunctional epoxy resins are used, the content of monofunctional epoxy resins refers to their total amount.
[0061] <(B) Component>
[0062] The component (B) contained in the conductive paste of the present invention is a latent curing agent. Here, the latent curing agent refers to a curing agent that can ensure storage stability, such as having little change in viscosity and physical properties over time when dispersed in the component (A).
[0063] As long as the (B) component has the properties as described above and cures the epoxy resin ((A) component), there is no particular limitation. From the perspective of storage stability and curability, a thermal latent curing agent (a compound with thermal curability) is preferred. As a thermal latent curing agent, for example, imidazole compounds, addition-type latent curing agents (reaction products obtained by reacting amine compounds with epoxy compounds, isocyanate compounds or urea compounds), dicyandiamide, hydrazide compounds, acid anhydrides, etc. can be cited. They can be used alone or in combination of two or more. The (B) component preferably includes at least one selected from the group consisting of the compounds listed above, and more preferably at least one selected from the group consisting of the compounds listed above. Among them, from the perspective of storage stability and curability, as the (B) component, it is preferred to include an addition-type latent curing agent, and more preferably an addition-type latent curing agent.
[0064] As the addition type latent curing agent, there is no particular limitation, and for example, a reaction product obtained by reacting an amine compound with an isocyanate compound or a urea compound (urea addition type latent curing agent), a reaction product of an amine compound with an epoxy compound (epoxyamine addition type latent curing agent), etc. can be cited. They can be used alone, or two or more can be used in combination. Among them, from the balance between storage stability and curability, (B) component preferably includes a urea addition type latent curing agent, more preferably includes a urea addition type modified aliphatic polyamine type latent curing agent, and particularly preferably a urea addition type modified aliphatic polyamine type latent curing agent.
[0065] Component (B) may be a liquid or a solid. From the viewpoint of storage stability, it is preferably a solid at 25°C. It should be noted that in this specification, "solid" means a state without fluidity at 25°C. Specifically, "solid" means a state of being non-fluid at 25°C using a cone-plate rotational viscometer at a shear rate of 10s -1 The state where the measured viscosity exceeds 1000 Pa·s; or the state where the fluidity is not present or the fluidity is extremely low and the above viscosity measurement cannot be performed.
[0066] Furthermore, in order to increase the contact area with the component (A) and improve the reactivity, the component (B) is preferably a powder. The average particle size of the powder is preferably 0.1 to 30 μm, more preferably 0.5 to 20 μm, particularly preferably 1 to 10 μm, and most preferably 3 to 8 μm. Here, the average particle size of the component (B) is the particle size (D50) when the cumulative volume ratio in the particle size distribution obtained by the laser diffraction scattering method is 50%.
[0067] As the latent curing agent of component (B), any of a synthetic product or a commercial product can be used. As a commercial product, it is not particularly limited, for example, as a urea addition type latent curing agent, Fujicure (registered trademark) FXE-1000, FXR-1020, FXR-1030, FXB-1050, FXR-1081 (T&KTOKA Co., Ltd.) etc. can be cited. Examples of epoxy amine addition type latent curing agents include Amicure (registered trademark) PN-23, Amicure PN-H, Amicure PN-31, Amicure PN-40, Amicure PN-50, Amicure PN-F, Amicure PN-23J, Amicure PN-31J, Amicure PN-40J, Amicure MY-24, Amicure MY-25, Amicure MY-R, and Amicure PN-R (manufactured by Ajinomoto Fine-Techno Co., Inc.) etc. These may be used alone or in combination of two or more.
[0068] Relative to 100 parts by mass of component (A) (when two or more compounds are used as component (A), the total amount is set to 100 parts by mass, the same below), the content of component (B) is preferably 1 to 100 parts by mass, more preferably 10 to 50 parts by mass, and most preferably 15 to 40 parts by mass. When the content of the above-mentioned component (B) is 1 part by mass or more, the curing property is excellent, and when it is 100 parts by mass or less, a conductive paste with excellent storage stability can be obtained. It should be noted that when two or more latent curing agents are used as component (B), the content of component (B) refers to their total amount.
[0069] <(C) Ingredients>
[0070] The component (C) contained in the conductive paste of the present invention is a plate-like crystalline metal powder (hereinafter also referred to as "crystalline metal powder") having an average particle size of 0.6 to 1.4 μm. Here, "crystalline metal powder" refers to a powder (metal powder) in which metal atoms are regularly and three-dimensionally arranged.
[0071] The crystalline metal powder used as component (C) is preferably a metal powder that can show conductivity. The material of such crystalline metal powder is not limited. For example, it can be appropriately selected from metal particles consisting of at least one metal selected from the group consisting of gold, silver, copper, nickel, palladium, platinum, tin, bismuth and the like; alloy particles composed of two or more selected from the above metals, etc. They can be used alone, or two or more can be used in combination. Among them, from the viewpoint of conductivity, cost, etc., the crystalline metal powder used as component (C) preferably contains metal particles consisting of at least one metal selected from the group consisting of gold, silver, copper, nickel, palladium, platinum, tin, and bismuth, more preferably contains silver particles, and particularly preferably silver particles.
[0072] Furthermore, component (C) is preferably a single crystal. A single crystal refers to a crystal in which single atoms or molecules are arranged in the same and regular direction. By being a single crystal, a conductive paste that provides a cured product with excellent conductivity can be obtained. From the viewpoint of further improving conductivity, the crystalline metal powder as component (C) preferably includes silver particles as single crystals.
[0073] The crystalline metal powder as component (C) has a plate-like shape (plate-shaped). In this specification, "plate-like shape (plate-shaped)" refers to a shape having two smooth surfaces and whose thickness (distance between the smooth surfaces) is substantially (approximately or completely) uniform. In other words, it refers to a shape in which the upper and lower smooth surfaces are substantially (approximately or completely) parallel. The shape and surface state of the powder (crystalline metal powder) can be confirmed by general means such as a scanning electron microscope (SEM).
[0074] In the above, for the "smooth surface", as an example, the arithmetic mean roughness Ra of the surface can be 10.0 nm or less. Furthermore, the arithmetic mean roughness Ra of the surface of the crystalline metal powder is more preferably 8.0 nm or less, and further preferably 3.5 nm or less (the lower limit is 0 nm). In addition, the arithmetic mean roughness Ra of the surface of the crystalline metal powder is preferably 1.0 nm or more. That is, as preferred examples of the range of the arithmetic mean roughness of the surface of the crystalline metal powder, 1.0 to 10.0 nm, 1.0 to 8.0 nm, 1.0 to 3.5 nm, etc. can be cited, but it is not limited to these. In this specification, the arithmetic mean roughness Ra of the surface of the crystalline metal powder can be evaluated using an atomic force microscope (AFM). As an example of a method for measuring the arithmetic mean roughness Ra of the surface of a crystalline metal powder, there can be cited the method described in paragraphs "0023" to "0025" of Japanese Patent Application Publication No. 2014-196527 (corresponding to paragraphs "0029" to "0036" of the specification of U.S. Patent Application Publication No. 2016 / 0001362). More specifically, as an example of a method for measuring the arithmetic mean roughness Ra of the surface of a crystalline metal powder, there can be cited the following method: using a scanning probe microscope SPM-9600 manufactured by Shimadzu Corporation, for example, under the following measurement conditions, the arithmetic mean roughness of 10 randomly selected particles at a measurement distance of 1 μm in the flattest surface (when it is difficult to measure at a distance of 1 μm in the flattest surface, the measurement is performed at a distance as large as possible in the plane), and the average value of these 10 arithmetic mean roughnesses is calculated, and the calculated value is used as the arithmetic mean roughness Ra of the surface of the crystalline metal powder.
[0075] 《Measurement conditions》
[0076] Mode: Contact mode
[0077] Cantilever: OMCL-TR800PSA-1 manufactured by Olympus Corporation
[0078] Resolution: 512×512 pixels
[0079] Height resolution: 0.01nm
[0080] Lateral resolution: 0.2nm.
[0081] In addition, in the above, "the thickness is substantially (approximately or completely) uniform" means that the deviation of the thickness is within the range of ±10% relative to the thickness of the powder (crystalline metal powder), and more preferably within the range of ±5%. It should be noted that the deviation of the thickness is determined by measuring the thickness of 1 (1 particle) powder (crystalline metal powder) at 3 points using a scanning electron microscope (SEM) and calculating the average value. In addition, as an example of a plate-like morphology, there is a morphology in which the aspect ratio (average particle size (D50) / average thickness (T)) described later is 3 to 100. As an example of a plate-like morphology, polygonal plates such as triangular plates, quadrilateral plates, pentagonal plates, hexagonal plates, and truncated triangular plates can be cited.
[0082] The average particle size of the component (C) is 0.6 to 1.4 μm, preferably 0.7 to 1.3 μm, more preferably 0.8 to 1.2 μm, and particularly preferably 0.9 to 1.1 μm. If the average particle size is 0.6 μm or more, a cured product with excellent conductivity can be obtained, and if it is 1.4 μm or less, a cured product with excellent conductivity and adhesion can be obtained. When the average particle size of the crystalline metal powder corresponding to the component (C) is less than 0.6 μm, the conductivity of the cured product obtained from the conductive paste decreases (Comparative Example 2 described later). When the average particle size exceeds 1.4 μm, there is a tendency that not only the adhesion but also the conductivity decreases (Comparative Examples 3 and 4 described later). Here, the average particle size of the component (C) is the particle size (D50) when the cumulative volume ratio in the particle size distribution obtained by the laser diffraction scattering method is 50%. As an example, the average particle size (D50) described in this specification can be measured using a laser diffraction particle size distribution analyzer (LA-950V2) manufactured by Horiba, Ltd.
[0083] The thickness (average thickness, T) of the (C) component is not particularly limited. From the perspective of further improving the conductivity and adhesion of the cured product, it is preferably 10 to 200 nm, more preferably 20 to 150 nm, and particularly preferably 30 to 120 nm. The thickness (average thickness, T) of the (C) component is obtained by randomly selecting 100 crystalline metal powders and measuring the thickness of each, and calculating the average value. The thickness of each crystalline metal powder is measured based on a SEM photograph.
[0084] The aspect ratio (average particle size (D50) / average thickness (T)) of component (C) is also not particularly limited. From the viewpoint of further improving the conductivity and adhesion of the cured product, it is preferably 5 to 100, more preferably 8 to 50, particularly preferably 10 to 35, and most preferably 15 to 30.
[0085] The specific surface area of the component (C) is also not particularly limited, but is preferably 0.1 to 1.8 m 2 / g, more preferably 0.3 to 1.6 m2 / g, particularly preferably 0.5 to 1.5 m 2 / g, the most preferred is 0.8m 2 / g or more and less than 1.1m 2 / g. Specific surface area is 0.1m 2 / g or more, the conductivity and adhesion are further improved, and the specific surface area is 1.8m 2 When the specific surface area is 2.347 W / g or less, a conductive paste having excellent conductivity and handling properties can be obtained. Here, the specific surface area is a value calculated by the BET method.
[0086] Furthermore, from the viewpoint of improving the conductivity and adhesiveness of the cured product in a balanced manner, in one embodiment, the average particle size (D50) of the component (C) is preferably 0.6 to 1.4 μm, and the specific surface area is preferably 0.1 to 1.8 m 2 In one embodiment, it is preferred that the average particle size (D50) of the component (C) is 0.7 to 1.3 μm, and the specific surface area is 0.3 to 1.6 m 2 In one embodiment, it is preferred that the average particle size (D50) of the component (C) is 0.8 to 1.2 μm, and the specific surface area is 0.5 to 1.5 m 2 In one embodiment, it is preferred that the average particle size (D50) of the component (C) is 0.9 to 1.1 μm, and the specific surface area is 0.8 m 2 / g or more and less than 1.1m 2 / g.
[0087] In addition, the surface of the crystalline metal powder as (C) component can be treated (surface treated) with a lubricant. As a lubricant, saturated fatty acids and / or unsaturated fatty acids can be used. For example, caproic acid, capric acid, undecanoic acid, lauric acid, tridecanoic acid, myristic acid, pentadecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, linolenic acid, linoleic acid, palmitoleic acid and oleic acid can be cited. Among them, from the perspective of excellent dispersibility and storage stability, the lubricant preferably includes a saturated fatty acid, more preferably includes at least one selected from caproic acid, lauric acid, palmitic acid and stearic acid, particularly preferably includes stearic acid, and most preferably stearic acid. They can be used alone, or two or more can be used in combination.
[0088] The crystalline metal powder as component (C) may be a synthetic product or a commercial product. Component (C) may be produced by a known production method, for example, the production method disclosed in Japanese Unexamined Patent Publication No. 2014-196527 (corresponding to U.S. Patent Application Publication No. 2016 / 0001362).
[0089] (C) As a commercial item of a component, there is no restriction|limiting in particular, For example, LM1 (made by Tokusen Kogyo Co., Ltd.) etc. are mentioned.
[0090] The content of component (C) is preferably 10 to 500 parts by mass, more preferably 20 to 300 parts by mass, more preferably 20 to 200 parts by mass, further preferably 20 to 150 parts by mass, further preferably 30 to 100 parts by mass, particularly preferably 50 to 100 parts by mass, and most preferably 70 to 90 parts by mass, relative to 100 parts by mass of component (A). When the content of the above-mentioned component (C) is 10 parts by mass or more, the conductivity and adhesion of the cured product are further improved, and when it is 500 parts by mass or less, a conductive paste with excellent operability can be obtained. It should be noted that when two or more crystalline metal powders are used as component (C), the content of component (C) refers to their total amount.
[0091] <(D) Component>
[0092] The conductive paste of the present invention may further contain metal powder other than the component (C) as the component (D). The component (D) can further improve the conductivity by combining with the component (C) of the present invention.
[0093] The material of the metal powder used as the component (D) is not limited, and can be appropriately selected from metal particles composed of at least one metal selected from gold, silver, copper, nickel, palladium, platinum, tin, bismuth, etc.; alloy particles composed of two or more selected from the above metals; particles formed by coating the surface with the above metal as a coating layer (particles having a coating layer composed of at least one metal selected from the above metals), etc. These can be used alone or in combination of two or more.
[0094] From the viewpoint of conductivity, cost, etc., the component (D) preferably includes: metal particles composed of at least one metal selected from the group consisting of gold, silver, copper, nickel, palladium, platinum, tin, and bismuth; and / or particles having a coating layer composed of at least one metal selected from the group consisting of gold, silver, copper, nickel, palladium, platinum, tin, and bismuth, more preferably silver particles and / or particles coated with silver (particles having a coating layer composed of silver), further preferably silver particles and particles coated with silver (particles having a coating layer composed of silver), and particularly preferably silver particles and particles coated with silver (particles having a coating layer composed of silver). The mass ratio of silver particles to particles coated with silver (mass of silver particles: mass of particles coated with silver) is preferably 90:10 to 30:70, more preferably 80:20 to 40:60, further preferably 70:30 to 50:50, particularly preferably 60:40 to 50:50, and most preferably 55:45 to 50:50.
[0095] As the shape of the component (D), there can be spherical (as an example, a perfect sphere), amorphous, flake (scaly), filament (needle), and dendrite. Among them, from the viewpoint of increasing the specific surface area and improving the conductivity, the shape of the metal powder of the component (D) is preferably spherical (especially a perfect sphere) or flake (scaly). In one embodiment, the silver particles as the component (D) are preferably flake-shaped, and the particles coated with silver are spherical (preferably a perfect sphere).
[0096] Furthermore, component (D) is preferably non-crystalline. That is, component (D) is preferably non-crystalline metal powder. Here, "non-crystalline metal powder" refers to metal powder other than the above-mentioned "crystalline metal powder". In addition, the surface of the metal powder as component (D) can be treated (surface treated) with a lubricant. As a lubricant, saturated fatty acids and / or unsaturated fatty acids can be used. For example, caproic acid, capric acid, undecanoic acid, lauric acid, tridecanoic acid, myristic acid, pentadecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, linolenic acid, linoleic acid, palmitoleic acid, oleic acid, etc. can be cited. From the perspective of excellent dispersibility and storage stability, the lubricant preferably contains saturated fatty acids, more preferably contains at least one selected from caproic acid, lauric acid, palmitic acid and stearic acid, particularly preferably contains stearic acid, and most preferably stearic acid. They can be used alone, or two or more can be used in combination.
[0097] In one embodiment, the average particle size of the component (D) is preferably 0.1 to 30 μm, more preferably 0.5 to 10 μm, and particularly preferably 1.5 to 5 μm. In addition, in another embodiment, the average particle size of the component (D) is preferably 0.1 μm or more and less than 0.6 μm or more than 1.4 μm and less than 30 μm, more preferably more than 1.4 μm and less than 20 μm, further preferably 1.5 to 10 μm, and particularly preferably 1.5 to 4 μm. Here, the average particle size of the component (D) is the particle size (D50) when the cumulative volume ratio in the particle size distribution obtained by the laser diffraction scattering method is 50%.
[0098] As a commercial item of (D)component, SILBEST (registered trademark) TC-770 (made by Tokuri Honten Co., Ltd.) etc. are mentioned, for example.
[0099] The content of component (D) is preferably 50 to 500 parts by mass, more preferably 100 to 400 parts by mass, further preferably 130 to 300 parts by mass, particularly preferably 150 to 200 parts by mass, and most preferably 150 to 180 parts by mass relative to 100 parts by mass of component (A). In addition, in other embodiments, the content of component (D) is particularly preferably 135 to 200 parts by mass, and most preferably 140 to 180 parts by mass relative to 100 parts by mass of component (A). When the content of the above-mentioned component (D) is 50 parts by mass or more, the conductivity is further improved, and when it is 500 parts by mass or less, a conductive paste with excellent operability can be obtained. It should be noted that when two or more metal powders are used as component (D), the content of component (D) refers to their total amount.
[0100] The mass ratio of component (C) to component (D) (mass of component (C) : mass of component (D)) is preferably 5:95 to 80:20, more preferably 10:90 to 60:40, further preferably 15:85 to 50:50, particularly preferably 20:80 to 45:55, and most preferably 30:70 to 40:60, from the perspective of obtaining a conductive paste that provides a cured product with excellent conductivity.
[0101] The total content of the components (C) and (D) is preferably 40% to 90% by mass, more preferably 50% to 80% by mass, and particularly preferably 55% to 75% by mass, relative to the entire conductive paste (the total mass of the conductive paste is 100% by mass). When the total content of the components (C) and (D) is 40% by mass or more, the conductivity of the cured product is further improved, and when it is 90% by mass or less, a conductive paste with excellent workability can be obtained.
[0102] When the total amount of components (A) to (C) is 100 parts by mass, the content of component (D) is preferably 40 to 300 parts by mass, more preferably 45 to 200 parts by mass, further preferably 50 to 150 parts by mass, particularly preferably 60 to 100 parts by mass, and most preferably 70 to 90 parts by mass relative to 100 parts by mass of the total amount of components (A) to (C). When the content of component (D) is 40 parts by mass or more relative to 100 parts by mass of the total amount of components (A) to (C), the conductivity of the cured product is further improved, and when it is 300 parts by mass or less, a conductive paste having excellent workability can be obtained.
[0103] <Organic Solvents>
[0104] The conductive paste of the present invention preferably contains substantially no organic solvent, more preferably contains no organic solvent (content: 0 mass %). Here, "substantially no organic solvent" means that the amount of organic solvent added (compounding amount) is less than 0.1 mass % relative to the total mass of the conductive paste. When the conductive paste contains a solvent, the organic solvent dissolves the (B) component and causes a decrease in storage stability and separation of the organic solvent, which may affect the physical properties. When an organic solvent is contained, the content of the organic solvent is preferably 1 mass % or less, more preferably 0.5 mass % or less, and most preferably 0.1 mass % or less (lower limit: 0 mass %) relative to the entire conductive paste (the total mass of the conductive paste is set to 100 mass %). If the content of the above-mentioned organic solvent is 1 mass % or less, the deterioration of storage stability and separation can be effectively suppressed.
[0105] Examples of the organic solvent include aromatic organic solvents such as toluene and xylene; aliphatic hydrocarbon organic solvents such as n-hexane; alicyclic hydrocarbon organic solvents such as cyclohexane, methylcyclohexane, and ethylcyclohexane; ketone organic solvents such as acetone and methyl ethyl ketone; alcohol organic solvents such as methanol and ethanol; ester organic solvents such as ethyl acetate and butyl acetate; and propylene glycol ether organic solvents such as propylene glycol methyl ether, propylene glycol ethyl ether, and propylene glycol tert-butyl ether. In one embodiment, the conductive paste of the present invention preferably does not substantially contain the organic solvents listed above, and more preferably does not contain (content: 0% by mass).
[0106] <Optional Ingredients>
[0107] In the conductive paste of the present invention, in addition to the above-mentioned components, various additives can be added as arbitrary components as needed within the scope of not damaging the effect of the present invention. As such additives, for example, silane coupling agents, plasticizers, fillers (excluding (C), (D) components), storage stabilizers, tackifiers, metal complexes (preferably organic metal complexes), resins (excluding (A) components), organic or inorganic pigments, rust inhibitors, defoamers, dispersants, surfactants, viscoelasticity regulators, thickeners can be cited. Among them, as an arbitrary component, it is preferred to include at least one selected from silane coupling agents, fillers, storage stabilizers, metal complexes (preferably organic metal complexes) and resins, more preferably including at least one selected from fillers, storage stabilizers, metal complexes (preferably organic metal complexes) and resins, further more preferably including at least two selected from fillers, storage stabilizers, metal complexes (preferably organic metal complexes) and resins, further more preferably including at least one selected from fillers, storage stabilizers, metal complexes (preferably organic metal complexes) and resins, further more preferably including at least one selected from fillers, storage stabilizers and resins, particularly preferably including fillers and storage stabilizers, and most preferably including fillers, storage stabilizers and resins.
[0108] (Silane coupling agent)
[0109] The conductive paste of the present invention may contain a silane coupling agent. Examples of the silane coupling agent include glycidyl-containing silane coupling agents such as 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 3-glycidoxypropylmethyldiethoxysilane; vinyl-containing silane coupling agents such as vinyltri(β-methoxyethoxy)silane, vinyltriethoxysilane, and vinyltrimethoxysilane; and γ-methacryloxysilane. Silane coupling agents containing (meth)acryloyl groups, such as propyltrimethoxysilane; silane coupling agents containing amino groups, such as N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and N-phenyl-γ-aminopropyltrimethoxysilane; γ-mercaptopropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, and their oligomers, etc., are preferably silane coupling agents containing glycidyl groups from the perspective of excellent adhesion. It should be noted that silane coupling agents containing glycidyl groups (i.e., compounds containing epoxy groups and silicon atoms) are not included in the (A) component of the present invention, but are disposed as silane coupling agents (i.e., one of the arbitrary components). They can be used alone, or two or more thereof can be used in combination.
[0110] There are no particular limitations on commercially available products of the silane coupling agent, and examples thereof include KBM-1003, KBE-1003, KBM-303, KBM-403, KBE-403, KBM-502, KBE-502, KBM-503, KBE-503, KBM-5103, KBM-1403, KBM-602, KBM-603, KBM-903, KBE-903 (manufactured by Shin-Etsu Chemical Co., Ltd.), Z-6610, Z-6044, Z-6825, Z-6033, and Z-6062 (manufactured by Dow Corning Toray Co., Ltd.).
[0111] (Bulking Agent)
[0112] The conductive paste of the present invention may contain fillers other than the components (C) and (D). Examples of fillers include glass, silica, talc, mica, ceramics, calcium carbonate, carbon powder, kaolin, dry clay minerals, dry diatomaceous earth, rubber particles, etc. From the viewpoint of being able to effectively suppress the decrease in conductivity of the cured product, when a filler is used, rubber particles are preferred as the filler. That is, the conductive paste of the present invention preferably contains rubber particles in addition to the above-mentioned components (A) to (C) and the component (D) added as needed.
[0113] In this specification, "rubber particles" refer to particles containing a layer showing rubber elasticity. The rubber particles may be particles consisting of only one layer showing rubber elasticity, or may be core-shell particles having at least one layer showing rubber elasticity and being a multilayer structure. Although the reason is unclear, from the viewpoint of excellent resin resistance (also called volume resistivity), rubber particles as fillers are preferably core-shell particles. In addition, rubber particles dispersed in epoxy resin (epoxy resin as component (A)) in advance may also be used. Here, the method for dispersing rubber particles in epoxy resin is the same as described in the above-mentioned <Component (A)>. As polymers constituting rubber particles as fillers, for example, butadiene rubber, acrylic rubber, silicone rubber, butyl rubber, olefin rubber, styrene rubber, NBR, SBR, IR, EPR, etc. may be used. They may be used alone or in combination of two or more. The rubber particles as fillers are preferably rubber particles containing at least one polymer selected from the polymers listed above. As an example, the rubber particles as fillers preferably contain rubber particles containing acrylic rubber, and more preferably rubber particles containing acrylic rubber. The rubber particles containing acrylic rubber are not particularly limited. As the rubber particles containing acrylic rubber, for example, rubber particles having a core-shell structure and containing acrylic rubber can be cited. It should be noted that, in this specification, "acrylic rubber" refers to a (co)polymer having a structural unit derived from acrylic acid ester (acrylate) and / or methacrylic acid ester (methacrylate), preferably a (co)polymer of acrylic acid ester and / or methacrylate.
[0114] Core-shell particles refer to microparticles in which the core (nucleus) and shell (wall) of the particles are composed of polymers of different properties. The preferred method for producing core-shell particles (powder particles) used in the present invention is as follows: First, polymerize the polymerizable monomers that form the core portion. Examples of the polymerizable monomers include (meth)acrylate monomers such as n-propyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-decyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 2-butoxyethyl (meth)acrylate; aromatic vinyl compounds such as styrene, vinyltoluene, and α-methylstyrene; vinyl cyanide compounds such as acrylonitrile, methacrylonitrile, and vinylene cyanide; 2-hydroxyethyl fumarate, hydroxybutyl vinyl ether, and monobutyl maleate. Furthermore, as examples of polymerizable monomers, crosslinking monomers having more than two reactive groups, such as ethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, hexanediol di(meth)acrylate, hexanediol tri(meth)acrylate, oligoethylene di(meth)acrylate, oligoethylene tri(meth)acrylate, etc., can be cited; aromatic divinyl monomers such as divinylbenzene; triallyl trimellitate, triallyl isocyanelate, etc. The polymerizable monomer can be selected to use one or more different types. Next, the polymer particles obtained using the polymerizable monomers exemplified above are used as the core, and the polymerizable monomers are further polymerized in a manner different from the composition of the core to form a second polymerization of a shell composed of a polymer having a melting point above room temperature. As the polymerizable monomer used at this time, the same polymerizable monomer as the polymerizable monomer used to obtain the above-mentioned core can be cited, and it can be selected from them for use. Preferred examples of polymerizable monomers used as shell materials include (meth)acrylates having an alkyl group (alkyl group bonded to a (meth)acryloyloxy group) having 1 to 4 carbon atoms, such as ethyl (meth)acrylate, n-butyl acrylate, methyl methacrylate, and butyl methacrylate.
[0115] The core-shell particles can be synthesized, for example, by the above-mentioned method, or commercially available products can be used. Commercially available products of the core-shell particles are not particularly limited, and examples thereof include PARALOID EXL-2655 (manufactured by Dow Chemical Japan Co., Ltd.) composed of a butadiene-alkyl methacrylate-styrene copolymer, Staphyloid (registered trademark, hereinafter the same) AC-3355, Staphyloid AC3364, Staphyloid TR-2105, Staphyloid TR-2102, Staphyloid TR-2122, Staphyloid IM-101, Staphyloid IM-203, Staphyloid IM-301, Staphyloid IM-401, and Staphyloid IM-406 composed of an acrylate-acrylonitrile-styrene copolymer, Staphyloid IM-601 composed of an acrylate-acrylonitrile-styrene copolymer, ZEFIAC (registered trademark) F-351G (manufactured by Aica Kogyo Co., Ltd.) composed of a polymethacrylate-based polymer, PARALOID EXL-2314, EXL-2611, EXL-3387 (made by Dow Chemical Japan Co., Ltd.), etc. They can be used alone or in combination of two or more. From the viewpoint that a small amount of addition can easily obtain the effect, the rubber particles as fillers preferably include (meth) acrylic core-shell particles, the (meth) acrylic core-shell particles including at least one selected from acrylate-methacrylate copolymers and polymethacrylate polymers, more preferably (meth) acrylic core-shell particles containing polymethacrylate polymers, and particularly preferably (meth) acrylic core-shell particles containing polymethacrylate polymers.
[0116] The average particle size of the rubber particles is preferably 0.01 to 10 μm, particularly preferably 0.05 to 5 μm. When the average particle size is 0.01 μm or more, the viscosity of the conductive paste can be suppressed from increasing, and when the average particle size is 10 μm or less, a conductive paste that provides a cured product with excellent conductivity can be obtained. Here, the average particle size of the rubber particles is the particle size (D50) at a cumulative volume ratio of 50% in a particle size distribution determined by a laser diffraction scattering method.
[0117] The content of the rubber particles is preferably 0.01 to 20 parts by mass, more preferably 0.05 to 10 parts by mass, and particularly preferably 0.08 to 3 parts by mass relative to 100 parts by mass of the component (A). When the content of the rubber particles is 0.01 parts by mass or more, the conductivity of the cured product is further improved, and when the content is 20 parts by mass or less, a conductive paste with excellent workability can be obtained. It should be noted that when two or more types of rubber particles are used, the content of the rubber particles refers to their total amount.
[0118] (Storage stabilizer)
[0119] The conductive paste of the present invention may contain a storage stabilizer. As a storage stabilizer, there is no particular limitation as long as the storage stability of the conductive paste is improved, and borate compounds, phosphoric acid, alkyl phosphates, p-toluenesulfonic acid, methyl p-toluenesulfonate, etc. may be used. As borate compounds, for example, trimethyl borate, triethyl borate, tri-n-propyl borate, triisopropyl borate, tributyl borate, trihexyl borate, tri-n-octyl borate, tri(2-ethylhexyloxy)borane, triphenyl borate, trimethoxyboroxine, 2,2'-carbonylbisoxybis-1,3,2-dioxaborolane-4,5-dione, etc. In addition, as a commercially available product of a borate compound, for example, "CUREDUCT L-07N" (manufactured by Shikoku Chemical Industry Co., Ltd.) can be cited. As alkyl phosphate, trimethyl phosphate, tributyl phosphate, etc. can be used, but are not limited to these. Storage stabilizers can be used alone or in combination. If storage stability is considered, the storage stabilizer preferably includes at least one selected from phosphoric acid, borate compounds (as an example, tributyl borate, trimethoxy boroxine) and methyl p-toluenesulfonate, and more preferably includes borate compounds. It should be noted that the storage stabilizer can use a storage stabilizer dispersed in an epoxy resin or a phenolic resin. In this way, when using a storage stabilizer dispersed in an epoxy resin, the epoxy resin is included in component (A).
[0120] The content of the storage stabilizer is preferably 0.01 to 10 parts by mass, more preferably 0.03 to 5 parts by mass, and particularly preferably 0.05 to 1 part by mass relative to 100 parts by mass of component (A). When the content of the above-mentioned storage stabilizer is 0.01 parts by mass or more, the effect of the storage stabilizer can be fully obtained, and when it is 10 parts by mass or less, a conductive paste with excellent workability can be obtained. It should be noted that when two or more storage stabilizers are used, the content of the storage stabilizer refers to their total amount.
[0121] (Metal Complex)
[0122] The conductive paste of the present invention may contain a metal complex. As the metal complex, an organic metal complex is preferred. Although there is no clear reason, by making the conductive paste of the present invention contain an organic metal complex, the connection resistance value for the adherend containing nickel on the outermost surface is reduced. As the metal (central metal) contained in the organic metal complex, it is preferably a divalent or trivalent metal, and as such a metal, specifically, zinc, aluminum, iron, cobalt, nickel, tin, copper, etc. can be cited. By adding the above-mentioned organic metal complex with a divalent or trivalent metal, it is possible to obtain a conductive paste that further reduces the connection resistance even for an adherend with nickel on the outermost surface, and has better storage stability and operability.
[0123] In addition, the ligand of the organometallic complex is not particularly limited, and preferably comprises an organic ligand having an alkoxy group and / or a carboxylate group (-COO) and / or an amino group. Specifically, as the above-mentioned organic ligand, acetate, acetoacetate (acetylacetonate; acac), caproate, oleate, laurate, phthalocyaninate (phthalocyanine skeleton), etc. can be listed, but it is not limited to these. By adding the above-mentioned organometallic complex with an organic ligand, it is possible to obtain a conductive paste that further reduces the connection resistance even for an adherend with nickel on the most surface, and has better storage stability and handling properties.
[0124] Specific examples of the organometallic complex include copper oleate (divalent), zinc acetoacetate (zinc acetylacetonate) (divalent), aluminum acetoacetate (aluminum acetylacetonate) (trivalent), cobalt acetoacetate (cobalt acetylacetonate) (divalent), nickel acetate (divalent), nickel acetoacetate (nickel acetylacetonate) (divalent), iron phthalocyanine (divalent), dibutyltin dilaurate (divalent), etc., but are not limited to these. These can be used alone or in combination of two or more.
[0125] The organic metal complex can use any of synthetic products or commercial products. As commercially available organic metal complexes, NACEM zinc (zinc acetylacetonate (divalent)), NACEM aluminum (aluminum acetylacetonate (trivalent)), NACEM cobalt (II) (cobalt acetylacetonate (divalent)), NACEM nickel (nickel acetylacetonate (divalent)) and the like manufactured by Nippon Chemical Industry Co., Ltd. can be cited. In addition, KS-1260 (dibutyltin dilaurate (divalent) manufactured by Common Pharmaceutical Co., Ltd. can be cited, but it is not limited to these. They can be used alone, or two or more can be used in combination.
[0126] When the conductive paste includes a metal complex (organic metal complex), the total mass of the conductive paste is set to 100 mass%, and the content of the metal complex (organic metal complex) is preferably 0.001 to 5 mass%, more preferably 0.01 to 3 mass%, and particularly preferably 0.03 to 1 mass%. When the content of the above-mentioned metal complex (organic metal complex) is 0.001 mass% or more, the connection resistance value is further reduced, and when the content of the above-mentioned metal complex (organic metal complex) is 5 mass% or less, it is easy to maintain good storage stability. It should be noted that when two or more metal complexes (organic metal complexes) are used, the content of the metal complex (organic metal complex) refers to their total amount.
[0127] (resin)
[0128] The conductive paste of the present invention may contain a resin as an arbitrary component (excluding component (A)). As such a resin, for example, a phenol resin (preferably a novolac-type phenol resin such as a phenol novolac resin and a cresol novolac resin), a urea resin, a melamine resin, a (meth) acrylic resin, a vinyl ester resin, an unsaturated polyester resin, a bismaleimide resin, a polyurethane resin, and other thermosetting resins; a polyethylene resin, a polypropylene resin, an ethylene-propylene copolymer, an ethylene-vinyl acetate copolymer, a polyvinyl chloride resin, a polystyrene resin, a polyacrylonitrile resin, a polyamide resin, a polycarbonate resin, a thermoplastic polyurethane resin, and the like, but not limited to these. The resin may be used alone or in combination. Among them, from the viewpoint of obtaining a conductive paste having excellent curability, the resin included as an arbitrary component is preferably a thermosetting resin, more preferably a phenol resin, and particularly preferably a novolac-type phenol resin. When the conductive paste of the present invention contains a phenol resin (preferably a novolac-type phenol resin) as an arbitrary component, the storage stability is improved. When the storage stabilizer as an optional component is in a form dispersed in a phenol resin, the phenol resin (preferably a novolac-type phenol resin) contained therein is included in the resin as an optional component.
[0129] The content of the optional component resin is preferably 0.01 to 10 parts by mass, more preferably 0.03 to 5 parts by mass, and particularly preferably 0.05 to 1 part by mass, relative to 100 parts by mass of the component (A). When two or more resins are used, the content of the resin refers to the total amount thereof.
[0130] In a preferred embodiment, the conductive paste of the present invention is substantially composed of the above-mentioned (A) to (C) components, and at least one selected from the group consisting of the (D) component, a silane coupling agent, a filler, a storage stabilizer, a metal complex, and a resin (excluding the (A) component, the same below). In a preferred embodiment, the conductive paste of the present invention is substantially composed of the above-mentioned (A) to (D) components, and at least one selected from the group consisting of a silane coupling agent, a filler, a storage stabilizer, a metal complex, and a resin. In a preferred embodiment, the conductive paste of the present invention is substantially composed of the above-mentioned (A) to (D) components, and at least one selected from the group consisting of a filler, a storage stabilizer, a metal complex, and a resin. In a preferred embodiment, the conductive paste of the present invention is substantially composed of the above-mentioned (A) to (D) components, and at least two selected from the group consisting of a filler, a storage stabilizer, a metal complex, and a resin. In a preferred embodiment, the conductive paste of the present invention is substantially composed of the above-mentioned (A) to (D) components, and at least one selected from the group consisting of a filler, a storage stabilizer, and a resin. In a preferred embodiment, the conductive paste of the present invention consists essentially of the above-mentioned components (A) to (D), a filler, and a storage stabilizer. In a preferred embodiment, the conductive paste of the present invention consists essentially of the above-mentioned components (A) to (D), a filler, a storage stabilizer, and a resin.
[0131] In the above embodiment, "the conductive paste consists essentially of X" means that the total content of X exceeds 99 mass% (upper limit: 100 mass%) when the total mass of the conductive paste is 100 mass% (relative to the conductive paste). Preferably, the conductive paste consists of X (the above total content = 100 mass%). For example, “the conductive paste of the present invention is substantially composed of the above-mentioned components (A) to (C) and at least one selected from the group consisting of the component (D), a silane coupling agent, a filler, a storage stabilizer, a metal complex and a resin” means that: when the total mass of the conductive paste is set to 100 mass% (relative to the conductive paste), the total content (total added amount) of the above-mentioned components (A) to (D), the silane coupling agent, the filler, the storage stabilizer, the metal complex and the resin exceeds 99 mass% (upper limit: 100 mass%), and the conductive paste is preferably composed of the components (A) to (C) and at least one selected from the group consisting of the component (D), a silane coupling agent, a filler, a storage stabilizer and a metal complex (the above-mentioned total content = 100 mass%). In addition, “the conductive paste described in the present invention is substantially composed of the above-mentioned (A) to (D) components and at least one selected from a silane coupling agent, a filler, a storage stabilizer, a metal complex and a resin” means: when the total mass of the conductive paste is set to 100 mass% (relative to the conductive paste), the total content (total added amount) of the above-mentioned (A) to (D) components, silane coupling agent, filler, storage stabilizer, metal complex and resin exceeds 99 mass% (upper limit: 100 mass%), and the conductive paste is preferably composed of the (A) to (D) components and at least one selected from a silane coupling agent, a filler, a storage stabilizer, a metal complex and a resin (the above-mentioned total content = 100 mass%). In addition, “the conductive paste described in the present invention is substantially composed of the above-mentioned (A) to (D) components and at least one selected from fillers, storage stabilizers, metal complexes and resins” means: when the total mass of the conductive paste is set to 100 mass% (relative to the conductive paste), the total content (total added amount) of the above-mentioned (A) to (D) components, fillers, storage stabilizers, metal complexes and resins exceeds 99 mass% (upper limit: 100 mass%), and the conductive paste is preferably composed of (A) to (D) components and at least one selected from fillers, storage stabilizers, metal complexes and resins (the above-mentioned total content = 100 mass%).In addition, “the conductive paste described in the present invention is substantially composed of the above-mentioned (A) to (D) components and at least two selected from the group consisting of a filler, a storage stabilizer, a metal complex and a resin” means: when the total mass of the conductive paste is set to 100 mass% (relative to the conductive paste), the total content (total added amount) of the above-mentioned (A) to (D) components, filler, storage stabilizer, metal complex and resin exceeds 99 mass% (upper limit: 100 mass%), and the conductive paste is preferably composed of the (A) to (D) components and at least two selected from the group consisting of a filler, a storage stabilizer, a metal complex and a resin (the above-mentioned total content = 100 mass%). In addition, “the conductive paste described in the present invention is substantially composed of the above-mentioned (A) to (D) components and at least one selected from the filler, the storage stabilizer and the resin” means: when the total mass of the conductive paste is set to 100 mass% (relative to the conductive paste), the total content (total added amount) of the above-mentioned (A) to (D) components, the filler, the storage stabilizer and the resin exceeds 99 mass% (upper limit: 100 mass%), and the conductive paste is preferably composed of the (A) to (D) components and at least one selected from the filler, the storage stabilizer and the resin (the above-mentioned total content = 100 mass%). In addition, “the conductive paste described in the present invention is substantially composed of the above-mentioned (A) to (D) components, fillers and storage stabilizers” means: when the total mass of the conductive paste is set to 100 mass% (relative to the conductive paste), the total content (total added amount) of the above-mentioned (A) to (D) components, fillers and storage stabilizers exceeds 99 mass% (upper limit: 100 mass%), and the conductive paste is preferably composed of (A) to (D) components, fillers and storage stabilizers (the above-mentioned total content = 100 mass%). In addition, “the conductive paste described in the present invention is substantially composed of the above-mentioned (A) to (D) components, fillers, storage stabilizers and resins” means: when the total mass of the conductive paste is set to 100 mass% (relative to the conductive paste), the total content (total added amount) of the above-mentioned (A) to (D) components, fillers, storage stabilizers and resins exceeds 99 mass% (upper limit: 100 mass%), and the conductive paste is preferably composed of (A) to (D) components, fillers, storage stabilizers and resins (the above-mentioned total content = 100 mass%).
[0132] [Curing method and cured product]
[0133] The conductive paste of the present invention can be cured by heating, and can be cured even at low temperatures (less than 100° C.). Therefore, another aspect of the present invention can provide a cured product obtained by curing the conductive paste (cured product of the conductive paste).
[0134] The method for manufacturing the cured product (the method for curing the conductive paste) is not particularly limited, and a known method can be used. As an example, there is a method in which the conductive paste of the present invention is applied to an adherend and then heated to cure it. Therefore, in order to achieve good operability during coating, the conductive paste of the present invention is preferably a liquid (liquid state). As an example, the viscosity of the conductive paste at 25°C is preferably greater than 0.01 Pa·s and less than 1000 Pa·s, more preferably 0.1 to 500 Pa·s, further preferably 0.3 to 100 Pa·s, particularly preferably 0.5 to 50 Pa·s, and most preferably 1 to 20 Pa·s. It should be noted that in this specification, the viscosity of the conductive paste is measured at 25°C using a cone-plate rotational viscometer at a shear rate of 10s -1 The viscosity is measured.
[0135] When applying the conductive paste, the thickness of the coating film is not particularly limited and can be appropriately adjusted within the range that can bond the adherend. In addition, the heating conditions (curing conditions) are not particularly limited as long as they are conditions that can fully cure the conductive paste. As an example, in the heating conditions of the curing method of the conductive paste described in the present invention, the heating curing temperature is not particularly limited. For example, from the perspective of less damage to the component as the adherend, it is preferably a temperature of 45°C to 100°C, and more preferably 50°C to 95°C. The heating curing time is not particularly limited. In the case of a heating curing temperature of 45°C to 100°C, from the perspective of production efficiency of the manufacturing method using the conductive paste, it is preferably 10 minutes to 3 hours, and more preferably 30 minutes to 2 hours.
[0136] [Adhesive]
[0137] The conductive paste of the present invention and the cured product obtained by using the same can be used for electronic components that require conductivity, etc. In view of excellent conductivity and adhesion, the conductive paste and cured product of the present invention can be suitably used for adherends with nickel as the outermost surface having poor conductivity. Here, there is no particular restriction on the adherend with nickel as the outermost surface, and the adherend is mainly nickel-plated, for example, SPCC (cold-rolled steel sheet), stainless steel, copper components (wires, printed circuit (base) boards, etc.) after electrolytic plating or non-electrolytic plating can be cited.
[0138] Example
[0139] Next, the present invention is described in more detail by listing examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, the operation / test is carried out under an environment of 25° C. and 55% RH. It should be noted that, unless otherwise specified, the concentration and % represent the mass concentration and mass %, respectively, and unless otherwise specified, the ratio is set to the mass ratio.
[0140] [Examples 1 to 3 and Comparative Examples 1 to 4]
[0141] In order to prepare the conductive paste, the following components are prepared. Hereinafter, the conductive paste is also referred to as a "composition". It should be noted that the viscosity of each component shown below is expressed by using a cone-plate rotational viscometer at a shear rate of 10 s at 25°C and 55% RH. -1 The measured value.
[0142] (A) Ingredients: Epoxy resin
[0143] · EPICLON (registered trademark) EXA-835LV (mixture of bifunctional bisphenol A epoxy resin and bifunctional bisphenol F epoxy resin, mixing mass ratio 50:50, epoxy equivalent: 165 g / eq, viscosity (25°C): 2000 mPa·s (2 Pa·s), manufactured by DIC Corporation)
[0144] CARDURA (registered trademark) E10P (glycidyl neodecanoate (monofunctional epoxy resin), epoxy equivalent: 240 g / eq, viscosity (25°C): 7 mPa·s, monofunctional epoxy resin, manufactured by MOMENTIVE)
[0145] (B) Component: Latent curing agent
[0146] Fujicure (registered trademark) FXR-1081 (modified aliphatic polyamine latent curing agent (urea addition type modified aliphatic polyamine latent curing agent), average particle size: 5 μm, manufactured by T&K TOKA Co., Ltd.)
[0147] (C) Component: Crystalline metal powder with an average particle size of 0.6 to 1.4 μm
[0148] LM1 (single crystal, silver particles, plate-shaped, stearic acid surface treatment, average particle size (D50): 1.0 μm, average thickness (T): 60 nm, aspect ratio (D50 / T): 16.7, specific surface area: 1.0 m 2 / g, produced by Tokusen Kogyo Co., Ltd.)
[0149] (C)' component: crystalline metal powder other than (C) component
[0150] N300 (single crystal, silver particles, plate-shaped, stearic acid surface treatment, average particle size (D50): 0.4 μm, average thickness (T): 40 nm, aspect ratio (D50 / T): 10, specific surface area: 2.4 m 2 / g, Tokusen Kogyo Co., Ltd.)
[0151] M13 (single crystal, silver particles, plate-shaped, stearic acid surface treatment, average particle size (D50): 2.0 μm, average thickness (T): 50 nm, aspect ratio (D50 / T): 40, specific surface area: 1.1 m 2 / g, Tokusen Kogyo Co., Ltd.)
[0152] M27 (single crystal, silver particles, plate-shaped, stearic acid surface treatment, average particle size (D50): 4.5 μm, average thickness (T): 80 nm, aspect ratio (D50 / T): 56.3, specific surface area: 1.0 m 2 / g, Tokusen Kogyo Co., Ltd.)
[0153] (D) Component: Metal powder other than (C)
[0154] ・SILBEST TC-770 (Flake-shaped silver particles (amorphous), surface treated with stearic acid, average particle size (D50): 3.5 μm, manufactured by Tokuri Honten Co., Ltd.)
[0155] ·Silver coating powder general type (core agent: acrylic resin (20 mass%), film: silver (80 mass%), spherical shape, average particle size (D50): 2 μm, Mitsubishi Materials Corporation)
[0156] Any ingredient
[0157] Zefiac F-351G (filler, polymethacrylate core-shell particles, average particle size: 0.3 μm, manufactured by Aica Kogyo Co., Ltd.)
[0158] CUREDUCT (registered trademark) L-07N (storage stabilizer, epoxy-phenol-borate complex (containing bifunctional bisphenol A type epoxy resin: 91 mass %, phenol novolac resin: 4 mass %, 2,2'-(carbonyldioxy)bis(1,3,2-dioxaborolane-4,5-dione: 5 mass %), manufactured by Shikoku Chemical Industry Co., Ltd.).
[0159] The method for manufacturing the composition described in Examples 1 to 3 and Comparative Examples 1 to 4 is as follows. Weigh component (A), component (C) (or component (C)'), component (D) and any component, and stir for 30 minutes using a planetary mixer. Next, weigh component (B) and add it, and use a planetary mixer to further perform vacuum degassing for 30 minutes while stirring to obtain a conductive paste. The obtained conductive paste is liquid at 25°C. The detailed preparation amount (the amount of each component added) is in accordance with Table 1, and the units of the numerical values are all parts by mass. It should be noted that for each component, a blank column means that the component is not added (amount added: 0 parts by mass).
[0160] <Conductivity Test>
[0161] On a masking tape with a width of 10 mm and a thickness of 100 μm, 5 holes with a diameter of 5 mm and a spacing of 10 mm are opened along the length direction. The masking tape is attached to an electroless nickel-plated plate with a width of 25 mm, a length of 100 mm, and a thickness of 1.6 mm, and the composition is applied on the masking tape using a squeegee. When applying with a squeegee, be careful not to mix bubbles into the composition. Next, the masking tape is peeled off and the composition is cured by heating at 80°C for 60 minutes in a hot air drying oven. After the temperature of the test piece drops to room temperature, the needle-shaped electrodes of the dual-display multimeter are respectively contacted with the cured products of the adjacent compositions (two cured products formed at a distance of 10 mm apart), and the resistance value is measured. The obtained resistance value is recorded in Table 1 as "conductivity (Ω)". By such measurement, the resistance value (volume resistivity) of the solidified material (conductive paste) itself, the resistance value (connection resistance value) generated between the solidified material (conductive paste) and the electroless nickel plate, and the resistance value (volume resistivity) of the nickel plate itself are measured in a composite manner. The value of "conductivity (Ω)" is preferably 0.30Ω or less, and more preferably 0.20Ω or less (lower limit: 0.01Ω).
[0162] <Adhesion strength measurement>
[0163] A masking tape was attached to an electroless nickel-plated plate of 1.6 mm thick, 25 mm wide, and 100 mm long so as to have a width of 5 mm and a thickness of 50 μm. The composition was applied to the nickel-plated plate with the masking tape attached using a scraper to form a uniform coating film, and then the masking tape was peeled off. A ceramic chip is dropped vertically onto the coating from 1 cm above the coating to prepare a test piece (n=5). The test piece is heated to 80°C×60 minutes in a hot air drying furnace to cure the composition. After the temperature of the test piece drops to room temperature, the digital dynamometer with contacts is moved at 50 mm / min while the nickel-plated plate is fixed. The chip is pushed by the contacts in a direction perpendicular to the long side of the test piece to measure the "maximum strength (N)". The "bonding strength (MPa)" is calculated by converting the bonding area and judged by the following evaluation criteria. In order to prevent the adherend from falling off, it is preferably 20 MPa or more, more preferably 25 MPa or more (upper limit: 50 MPa).
[0164] [Table 1]
[0165]
[0166] Examples 1 to 3 are compositions containing components (A) to (C), respectively, and all of them were confirmed to have excellent conductivity and adhesion. On the other hand, Comparative Example 1 is a composition not containing component (C), and as a result, the conductivity and adhesion were poor. Comparative Examples 2 to 4 are compositions containing component (C)' with different characteristics instead of component (C), and as a result, although the adhesion was excellent, the conductivity was poor.
[0167] Industrial Applicability
[0168] The conductive paste and its cured product of the present invention have excellent conductivity and adhesiveness, and are therefore useful in the conduction / adhesion applications of electrical / electronic components that are being miniaturized in recent years, and can particularly reduce the resistance value of metals such as nickel that are prone to poor conductivity. Due to these characteristics, the present invention can be used for the assembly of various electrical / electronic components, and is likely to be expanded to a wide range of applications.
[0169] This application is based on Japanese Patent Application No. 2022-067363 filed on April 15, 2022, the disclosure of which is referenced and cited in the present specification in its entirety.
Claims
1. A conductive paste comprising the following components (A) to (C), (A) ingredient: epoxy resin; (B) component: latent curing agent; (C) Component: plate-like crystalline metal powder having an average particle size of 0.6 μm to 1.4 μm.
2. The conductive paste according to claim 1, wherein The (C) component is contained in an amount of 20 to 300 parts by mass based on 100 parts by mass of the (A) component.
3. The conductive paste according to claim 1 or 2, wherein The specific surface area of the component (C) is 0.1 m 2 / g~1.8m 2 / g. 4 . The conductive paste according to claim 1 , further comprising a metal powder other than the component (C) as a component (D).
5. The conductive paste according to claim 4, wherein The component (D) is contained in an amount of 50 to 500 parts by mass based on 100 parts by mass of the component (A).
6. The conductive paste according to claim 1 or 2, wherein The component (A) contains a monofunctional epoxy resin. 7 . The conductive paste according to claim 1 , further comprising rubber particles. 8 . A cured product obtained by curing the conductive paste according to claim 1 or 2.
